STATE ACTION AS AN INDIVIDUAL SECURITY THREAT IN CASE OF CYBERCRIME SECURITIZATION - Miftah Farid; Ajeng Ayu Adhisty (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2019)
In the current security concept, there are some changes to the current security object. This is due to the increasingly broad understanding of security objects.  This study examines the emergence of cyber issues as a new threat to state security. Cyber actions in the virtual world are developing along with the rapid technology development. Moreover, the state policy on cyber issues is considered as a new threat to individual security. The development of that state security issue is being debated among the theoreticians of international security studies. The concept of securitization explains the phenomenon of cyber issues and receives the attention of many states. Securitization carried out by the United States on Cybercrime issues becomes the initial trigger in viewing cyber actions as a new threat to state security. The object of this paper is more focused on State policy in dealing with cyber threats. Afterward, state policy in facing the cyber threat is seen from the perspective of human security from UNDP. Therefore, there is a debate about the desired security object. State actions to reach state security are then considered as individual privacy security. So, international security now does not only focus on state objects but also on individual, environment, economy, and identity. Thus, every action taken in securing an object does not pose a threat to other security objects.Keywords: Cybercrime, State Security, Human Security, Securitization